INFLUENCE OF CITY BRANDING, BRAND IDENTITY AND BRAND IMAGE ON VISITING DECISION TO KOTA PEKALONGAN - Ujianto Purwanto; Euis Soliha (Fakultas Ekonomi dan Bisnis Universitas Padjadjaran, 2017)
Recently, city branding become the most issue in marketing. The cities being developed to be the best destination for tourism, therefore, by city branding, it was not only to attract the tourist for visiting the city but also to make the city image. Regarding for this, Pekalongan city that had huge potential in batik, in the first april as the pekalongan 105 anniversary had launched the city branding for Pekalongan by the tag line